Prevalence of Measles in Adult Patients During Two Years in Infectious Disease Hospital Kabul Hospital, Afghanistan - Barakat, Mohammad Akmal; Mangal, Maail Khan (International Journal For Research In Health Sciences And Nursing, 2021)
BACKGROUND: Measles is one of the infectious diseases which is highly contagious and remain one of the leading causes of the death among young children .in 2015 there were 134200 measles death globally. Without immunization morbidity and mortality in recent years, are increasing number of adult measles has been recognized in Afghanistan and reported by the infectious disease hospital Kabul Afghanistan Measles characterized by a maculopapular rash. It continues to be a common and sometimes fatal disease in developing countries. In Afghanistan, it causes many outbreaks in areas with low vaccine coverage. Measles itself is one of the leading causes of death among young children and adults, even though a safe and cost-effective vaccine is available. Methods: This was two years hospital base, prospected record-based study, which done on adult patients who presented with measles to the infectious disease hospital, Kabul Afghanistan. we first analyzed data gathered by the Infectious Disease Hospital Kabul Afghanistan, in order to develop our understanding of causative factors that lead to the accumulation of susceptible individuals into foci this study based on data gathered in 2019 and 2020 at infectious disease hospital Kabul Afghanistan. In 2019 thirty-three patients came to hospital with measles diagnosis among thirty-three patients 10 were male (33%) and 23 patients were female (69.9%). In 2020 eight adult patients diagnosed with Measels 6 female (75%) and 2 Male (25%) A prospective study was carried out recruiting 41 adult patients with confirmed measles. infection who was managed at Infectious Disease Hospital Kabul Afghanistan. Demographic and clinical data were retrieved retrospectively using a predesigned questionnaire with the help of ward records. Some other relevant data were later obtained by interviewing patients during their clinic visits. Results: although it’s often associated with childhood illness, adults can get measles too. The patients present with high grade fever, severe body aches, sore throat, dry cough, red eyes and cervical lymphadenopathy over 5-6 days duration and late they developed maculo popular rash helping the diagnosis. They had variables degree of leucopenia, lymphocytosis, and thrombocytopenia, People who aren’t vaccinated are at a higher risk of catching the disease. It’s generally accepted that adults born during or before 1957 are naturally immune to measles.in this study that 41 patients diagnosed with measles all of them hospitalized with different hospital stay and all of them discharge from hospital with (0%) mortality rate. Conclusions: Communicable disease reporting systems can guide public health operations such as the implementation of new vaccines, and permit evaluation of health interventions. For example, measles supplementary immunization activities in Afghanistan have not slowed long-term transmission of the disease, but decreases in typhoid fever and acute viral hepatitis are probably tied to improvements in sanitation in the country.